Association of simple renal cysts with metabolic syndrome in adults - Wei-Chen Shen; Zih-Jie Sun; Zih-Jie Sun; Chieh-Ying Chou; Yu-Tsung Chou; Yu-Tsung Chou; Feng-Hwa Lu; Feng-Hwa Lu; Yi-Ching Yang; Yi-Ching Yang; Chih-Jen Chang; Chih-Jen Chang; et al. (Frontiers Media S.A., 2022)
Background and aimsMetabolic syndrome is common nowadays and may increase risk of hypertension, type 2 diabetes mellitus, cardiovascular complications and even mortality. Renal cysts are also frequently found during routine examination. However, the relationship between simple renal cysts (SRCs) and metabolic syndrome remains unclear. This study aimed to investigate the association of SRCs with metabolic syndrome.MethodsA total of 16,216 subjects aged ≥18 years were enrolled in this study. SRCs were diagnosed with ultrasonography by finding: sharp, thin posterior walls, a round/oval shape, absence of internal echoes, and posterior enhancement. SRCs were categorized by number (0, 1, and ≥2) and size (<2 and ≥2 cm). Metabolic syndrome was diagnosed according to the consensus statement from the International Diabetes Federation.ResultsIn multivariate analysis, SRCs were positively related to metabolic syndrome (OR: 1.18, 95% CI: 1.06-1.34). The risk of metabolic syndrome was higher for SRCs with a number ≥2 (OR: 1.35, 95% CI: 1.08-1.68) and size ≥2 cm (OR: 1.33, 95% CI: 1.10-1.61). When considering the SRC number and size concomitantly, SRCs with a number ≥2/size ≥2 cm (OR: 1.42, 95% CI: 1.02-1.98) or <2/size ≥2 cm (OR: 1.30, 95% CI: 1.04-1.62) were positively related to metabolic syndrome.ConclusionsSimple renal cysts were found to be related to a higher risk of metabolic syndrome, and the association is more significant in those with larger (sizes ≥2cm) or plural (numbers ≥2) SRCs.